Top 50 Grammar Mistakes How to Avoid Them - Wallwork, Adrian (Easy English!, 2018)
This book focuses on the most commonly made grammar mistakes by non-native English speakers. This means that you can set yourself a reasonable target. So rather than trying to learn all English grammar, just concentrate on those issues that tend to be used the most frequently and/or tend to create the most misunderstandings. Each chapter contains: Examples of typical mistakes. Examples of correct usage. Rules / explanations. A short exercise where you can immediately practise what you have learned. Additional exercises. Keys to all exercises. The book also contains a Teachers Introduction. Easy English! is a series of books to help you learn and revise your English with minimal effort. You can improve your English by reading texts in English that you might well normally read in your own language e.g. jokes, personality tests, lateral thinking games, wordsearches. doing short exercises to improve specific areas grammar and vocabulary, i.e. the areas that tend to lead to the most mistakes - the aim is just to focus on what you really need rather than overwhelming yourself with a mass of rules, many of which may have no practical daily value Other books in the Easy English!series include: Wordsearches: Widen Your Vocabulary in English Test Your Personality: Have Fun and Learn Useful Phrases Word games, Riddles and Logic Tests: Tax Your Brain and Boost Your English Top 50 Grammar Mistakes: How to Avoid Them Top 50 Vocabulary Mistakes: How to Avoid Them.